A review of Literature of coffee Research in Indonesia - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This document presents topics such as: 1.Plan of the study, 2.Early history, 3.Introduction of new species, 4.Technique of production, 5.The crop on estates, 6.Production by natives, 7.Leaf disease, 8.Other fungoid diseases, 9.pests of coffee, 10.Generative multiplication, 11.Vegetative propagation, 12.Growing the crop, 13.The shade problem, 14.Coffea arbica, 15.Varieties of arabica, 16.improvement of arabica coffee, 17.Coffea Lebérica and allied species, 18.Coffea Robusta, 19. The Robustoid kinds, 20.Improvement and degeneration of robusta, 21.The effect of selection onRobusta, 22.Various species, 23.The diversity of forms, 24.Chromosome studies, 25.Hybrids between distant species, 26.Hybrids within the group, 27.The market proiduct, 28.Byproducts of coffee, 29.Indonesian coffee in the market